ÐÐ½Ñ‚Ð¸Ñ„Ñ€Ð¸Ð·Ð½Ñ‹Ðµ Ð±ÐµÐ»ÐºÐ¸. Ð¡Ð¾Ð¾Ð±Ñ‰ÐµÐ½Ð¸Ðµ II. Ð Ð°ÑÐ¿Ñ€Ð¾ÑÑ‚Ñ€Ð°Ð½ÐµÐ½Ð¸Ðµ Ð² Ð¿Ñ€Ð¸Ñ€Ð¾Ð´Ðµ - Gulevsky, A. K.; Relina, L. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2009)
Multiple data on distribution of antifreeze proteins in nature are summarised in the paper. The main principles of their classification are presented. A variant of antifreeze protein classification depending on taxonomic categories of organisms, which they were found in, is proposed.